2020
DOI: 10.1002/jcb.29667
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of immune infiltration in lung adenocarcinoma and their clinical significant: A gene‐expression–based retrospective study

Abstract: Lung cancer is one of the fatal tumors. The tumor microenvironment plays a key role in regulating tumor progression. To figure out the role of tumor microenvironment in lung adenocarcinoma (LUAD), ESTIMATE algorithm was used to evaluate the immune scores in LUAD. Patients with low immune scores had a worse overall survival (OS) compared with high immune scores. Using RNA‐Seq data of 489 patients in The Cancer Genome Atlas (TCGA), differentially expressed genes (DEGs) were identified between high‐ and low‐immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…And LUAD, as the most common type of lung cancer, is able to account for more than half of the morbidity and mortality of the lung cancer patient. 28,29 Currently, growing evidence has suggested that TME plays a pivotal role in tumor initiation and progression, 27,30 especially the recent immunocheckpoint inhibitors have noticeable effects on lung adenocarcinoma. However, patient prognosis and disease progression involved with TME related genes in LUAD have not been elucidated clearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And LUAD, as the most common type of lung cancer, is able to account for more than half of the morbidity and mortality of the lung cancer patient. 28,29 Currently, growing evidence has suggested that TME plays a pivotal role in tumor initiation and progression, 27,30 especially the recent immunocheckpoint inhibitors have noticeable effects on lung adenocarcinoma. However, patient prognosis and disease progression involved with TME related genes in LUAD have not been elucidated clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, to explore the significance of these genes simultaneous changes for LUAD, we constructed and validated a risk assessment model that predicted survival of LUAD based on 106 genes.The prognostic model achieved robust predictive ability by combing with the clinical parameter we filtrated by multivariate Cox regression analysis.Recently, we notice that there are other prognostic model build by immune gene in LUAD 27 , however, compared with their prognostic model, the prognostic model we build have some advantages. First of all, we constructed the model by factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…High TMB indicates the presence of more neoantigens in the tumor microenvironment, which promote the in ammatory response and result in the alteration of transcriptomic and epigenetic signature [47]. It has been proved that gene expression signatures in the tumor microenvironment were associated with the prognosis in NSCLC [48][49][50][51]. In agreement with previous studies, the differentially expressed genes between TMB-H and TMB-L patients identi ed in this study were found to enrich in the immune-related damaged DNA binding, nuclear division, nuclear chromosome segregation, organelle ssion, single-stranded DNA binding, ribonucleoprotein complex binding and pyrimidine metabolism (Additional le 2: Figure S2) [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the TME, remodeling of the extracellular matrix (ECM), pro-and anti-inflammatory processes, and cell metabolism are affected by neoplastic progression, but they also affect further progression and metastasis of the tumor. These changes can be examined by evaluating particular inflammatory and metabolic markers, which, in turn, may be considered diagnostic biomarkers [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Created with BioRender.com and Affinity Designer. TME is a complex mixture of tumor cells, extracellular matrix, and an inflammatory microenvironment including immune cells and cytokines that plays an essential part in tumorigenesis and progression [14,17,27]. The unrestricted proliferation of cancer cells influences TME, manifesting itself, among other things, in increased glucose uptake.…”
Section: Introductionmentioning
confidence: 99%